Overflows in slam poetry: seeing, existing and occupying (Revista Apotheke, 2022)
Slam poetry takes its inspiration from sports. This is precisely what this text is about: poetry as a game in which the poem hits in different directions and causes overflows. The poems created for the competitions, which take place from North to South of Brazil, become possibilities of aesthetic and poetic displacements. From the studies of visual culture, we focus on three perspectives of the context of Brazilian slams groups, which we call overflows: the overflow of seeing, of existing and, finally, the overflowing of occupying. Our journey through these edges that are blurred and overflowed, lead us to a poetic movement that triggers aesthetic-educational processes, either by the occupation of places, by the re-existence of other bodies or by the insertion in online screens and in schools.
Keywords: Slam Poetry; Visual Culture; Overflow